A contractarian approach to actuarial fairness - Heras, Antonio (Journal of business ethics, 2025)
We defend, from a contractarian perspective, that the fair price of an insurance policy is the amount that the contracting parties agree when they are both equally uncertain about the insured event. Drawing on the approach developed by R. Sugden in The Community of Advantage, we answer two standard objections raised against contractarianism in the actuarial sciences: (1) people are not wise enough to assess their actuarial risks; (2) they are not rational enough to decide which insurance policy suits them better. We show under which circumstances people can make fair actuarial agreements, without presupposing any objective risk or rationality benchmarks.